2020
DOI: 10.1186/s12891-020-3151-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and nocturnal pain in patients with femoroacetabular impingement and acetabular dysplasia

Abstract: Background: Femoroacetabular impingement (FAI) syndrome and acetabular dysplasia (AD) are common pathologies that lead to pain in the young adult hip. Nocturnal pain in these patients is often reported, yet little is known regarding the effect of these hip pathologies on overall sleep quality. The purpose of this study was to evaluate sleep quality in patients with AD and FAI syndrome. Methods: This cross-sectional study consisted of 115 patients who complained of hip pain secondary to either FAI syndrome or A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…15 Reddy et al found that 79% of FAIS and 89% of acetabular dysplasia patients reported poor sleep quality based on the 19-question Pittsburgh Sleep Quality Index (PSQI). 16 Of the FAIS patients who had disrupted sleep in our study, the majority (59%) reported scores with moderate to severe levels of sleep disturbance. This is concerning, as both the prevalence and severity of chronic sleep dysfunction in FAIS patients may be underrecognized in a typical evaluation for FAIS by primary care physicians and orthopaedic surgeons.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…15 Reddy et al found that 79% of FAIS and 89% of acetabular dysplasia patients reported poor sleep quality based on the 19-question Pittsburgh Sleep Quality Index (PSQI). 16 Of the FAIS patients who had disrupted sleep in our study, the majority (59%) reported scores with moderate to severe levels of sleep disturbance. This is concerning, as both the prevalence and severity of chronic sleep dysfunction in FAIS patients may be underrecognized in a typical evaluation for FAIS by primary care physicians and orthopaedic surgeons.…”
Section: Discussionmentioning
confidence: 59%
“…Prior literature has recommended that patients with hip pain from FAIS or acetabular dysplasia pathology should potentially be screened for sleep disturbances and given considerations for a multidisciplinary treatment approach. 15,16 In most treatment algorithms of FAIS, there are no recommendations to address the chronic sleep dysfunction in these patients. [17][18][19][20][21][22] Most treatment modalities focus on addressing physical function with physical therapy for functional range of motion and strength training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] This has largely been determined by the Pittsburgh Sleep Quality Index (PSQI), which is a 7-item, subjective questionnaire that captures subjective sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disturbance, use of sleep medications, and daytime dysfunction. 13 Specifically pertaining to hip arthroscopy, Reddy et al 14 evaluated sleep quality in 115 patients with acetabular dysplasia and femoroacetabular impingement syndrome (FAIS) and found that patients on average had a PSQI of 8.46 (range, 0-21), indicating poor sleep quality. Likewise, our group reported that 94.2% of patients suffered from poor sleep quality before undergoing hip arthroscopy for FAIS, which decreased to 21.7% at 6 months postoperatively.…”
Section: See Commentary On Page 879mentioning
confidence: 99%
“…In nonarthritic individuals with femoroacetabular impingement (FAI) syndrome and acetabular dysplasia, sleep quality has been shown to be significantly affected. 12 Eighty-nine percent and 79% of patients with dysplasia and FAI syndrome report poor sleep quality, respectively. The latter was determined using the Pittsburgh Sleep Quality Index (PSQI) scale, with scores of 9.0 AE 4.4 and 8.0 AE 4.3, respectively.…”
Section: See Related Article On Page 873mentioning
confidence: 99%